Internal pressure test for composite marine riser - Kwoh, Boon How (2014)
An attempt to investigate behaviors of composite pipes subjected to internal pressure under open end pipe end conditions. The experiment shall be conducted in fixture mode 3. This is due to an expected limit condition of blowout, where the pipe is subjected to almost pure hoop stress. An experimental apparatus designed for closed end pipe testing was modified to this purpose by changing the sealing mechanism. Acoustic equipment and strain gauges were proposed but not used as the experiment’s aim was to validate the equipment. The pipe was subjected to pure hoop loading condition and experiment proceeded to 150bars where the seal failed. This was due to pipe radial expansion being greater than the sealing capacity. An analysis of mechanical properties and expected failure modes is presented to explain the properties of the composite pipe. Future recommendations have been made to aid further research.